LEGAL PROTECTION FOR HOME BUYERS AGAINST DEFAULT BY DEVELOPERS - Sizia, Aleynca; Khairi, Ilman; Ilyanawati, R. Yuniar Anisa (DE'RECHTSSTAAT, 2024)
Legal protection for home buyers is very important when developers default, one of which is by guaranteeing the house certificate that has been purchased to a third party, such as banks or other financial institutions. This practice is detrimental to buyers because it can cause the house certificate that should be the buyer's right to become collateral for the developer's debt. As a result, buyers risk losing the rights to the house they have purchased if the developer fails to pay off their debts. According to Consumer Protection Law No. 8 of 1999, these practices run counter to the idea of good faith in the agreement and infringe upon the rights of consumers. Buyers who suffer losses due to the developer's failure have the right to demand that their rights be fulfilled, that they be compensated, or that the agreement be cancelled, according to the Civil Code (KUHPer), particularly Articles 1320 and 1267. The goal of the guarantee cannot disregard the rights of other parties, such as homebuyers, as stated in Law No. 4 of 1996, which deals with Dependent Rights. Strict government oversight and openness in property purchasing and selling activities are necessary for more effective legal protection. Furthermore, in order to prevent any losses caused by developer default, purchasers are urged to exercise greater caution in verifying the certificate's legitimacy before to finalizing a deal.